2002
DOI: 10.1016/s0022-5347(05)64919-1
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Erectile Function after Brief Aggressive Antihypertensive Therapy

Abstract: The improvement in erectile function after brief aggressive treatment may be related to improvement in structurally based vascular resistance within the penis and the decrease in responsiveness of alpha1-adrenoceptor mediated erectolytic signaling. These findings are suggestive of a new therapeutic strategy for hypertension and erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 29 publications
7
45
0
1
Order By: Relevance
“…The ANS provides an environment that induces rat prostatic growth; the gland regresses in its absence. These findings were supported by additional animal studies using a strain of spontaneously hypertensive rats that developed increased autonomic activity, prostate hyperplasia, and ED [37][38][39]. Erectile function improved in this model after brief, aggressive treatment of the hypertension; this improvement may be related to improvement in structural vascular resistance within the penis and a decrease in responsiveness ofadrenoceptor-mediated erectolytic signaling.…”
Section: Autonomic Hyperactivitymentioning
confidence: 55%
“…The ANS provides an environment that induces rat prostatic growth; the gland regresses in its absence. These findings were supported by additional animal studies using a strain of spontaneously hypertensive rats that developed increased autonomic activity, prostate hyperplasia, and ED [37][38][39]. Erectile function improved in this model after brief, aggressive treatment of the hypertension; this improvement may be related to improvement in structural vascular resistance within the penis and a decrease in responsiveness ofadrenoceptor-mediated erectolytic signaling.…”
Section: Autonomic Hyperactivitymentioning
confidence: 55%
“…The four theories interrelating ED and LUTS are decreased or altered nitric oxide synthase and nitric oxide levels in the prostate and penile smooth muscle; autonomic hyperactivity effects on LUTS, prostate growth, and ED; increased Rho-kinase activation and endothelin activity affecting the alternate pathways of smooth muscle relaxation and contraction; and prostate and penile atherosclerosis [8, [10][11][12][13][14][15][16][17]. With studies showing an association between BPH and ejaculatory dysfunction and theories outlining the biologic plausibility of this association, understanding the impact of treating one condition on the outcome of the other is important.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rat model, McVary et al [39] demonstrated that the ANS provides an environment that induces rat prostatic growth, whereas its absence leads to glandular regression. These fi ndings were supported by additional animal studies using spontaneously hypertensive rats (SHR) that developed increased autonomic activity, prostate hyperplasia, and ED [40,41]. Following brief but aggressive hypertension treatment, erectile function improved [41].…”
Section: Autonomic Hyperactivity and Metabolic Syndrome Effects On Lumentioning
confidence: 91%
“…These fi ndings were supported by additional animal studies using spontaneously hypertensive rats (SHR) that developed increased autonomic activity, prostate hyperplasia, and ED [40,41]. Following brief but aggressive hypertension treatment, erectile function improved [41]. These effects may be related to improvement in structurally based vascular resistance within the penis and the decrease in responsiveness of α 1 -adrenoceptor-mediated erectolytic signaling.…”
Section: Autonomic Hyperactivity and Metabolic Syndrome Effects On Lumentioning
confidence: 91%